2015
DOI: 10.1097/ajp.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Multiple Facets of School Functioning in Pediatric Chronic Pain

Abstract: Anxiety was a robust predictor of school functioning across a range of domains. Evaluating anxiety symptoms in pediatric chronic pain will likely facilitate case conceptualization and treatment planning. This study supports a shift in focus from pain to anxiety as the driving force of school impairment in youth with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Emotional vulnerability in young children with chronic illness has been previously documented (Bell, Bayliss, Glauert, Harrison, & Ohan, ). Patients with pediatric chronic pain more frequently miss school or other academic activities because of their symptoms (Kahn et al, ) and are more likely to show signs of withdrawal and other internalizing tendencies (Pascali et al, ). Thus, while the sample as a whole does not appear to have significant psychological difficulties, it will be important for clinicians to identify those children who might be at risk for psychosocial difficulties and who would benefit from intervention services.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional vulnerability in young children with chronic illness has been previously documented (Bell, Bayliss, Glauert, Harrison, & Ohan, ). Patients with pediatric chronic pain more frequently miss school or other academic activities because of their symptoms (Kahn et al, ) and are more likely to show signs of withdrawal and other internalizing tendencies (Pascali et al, ). Thus, while the sample as a whole does not appear to have significant psychological difficulties, it will be important for clinicians to identify those children who might be at risk for psychosocial difficulties and who would benefit from intervention services.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing these factors in a group setting can help youth return to school and thereby improve school performance. In a study of 349 youth treated in a chronic pain clinic, Khan et al [34] found that anxiety played an important role in both school attendance and function while at school. Addressing anxiety, enhancing self-confidence and self-efficacy, and assisting teens in developing methods to manage anxiety using CBT, are all pillars of practice that are incorporated into our program.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, school absence rates in pediatric chronic pain possibly exceed rates of absenteeism due to other chronic health conditions [ 34 ]. Youth with chronic pain who frequently experience periods of missed school often fall behind academically as a result of their pain symptoms [ 18 , 23 , 35 , 37 , 38 ]. Chronic pain patients also report lower grades and other maladaptive school-related behaviors following the onset of pain [ 37 , 39 ].…”
Section: School-related Anxiety and Impairment In Pediatric Chronimentioning
confidence: 99%
“…Despite overwhelming evidence of school anxiety among pediatric pain patients [ 18 20 ], research focused specifically on the measurement of school anxiety symptoms remains largely undeveloped. There is a need for more tailored assessment strategies targeting school anxiety in pediatric chronic pain [ 20 23 ] as clarifying the nature and extent of school anxiety in pediatric chronic pain has important implications for theory, assessment, and intervention.…”
Section: Introductionmentioning
confidence: 99%